Cdx2 regulates immune cell infiltration in the intestine - Simon Chewchuk (Nature Portfolio, 2021)
Abstract The intestinal epithelium is a unique tissue, serving both as a barrier against pathogens and to conduct the end digestion and adsorption of nutrients. As regards the former, the intestinal epithelium contains a diverse repertoire of immune cells, including a variety of resident lymphocytes, macrophages and dendritic cells. These cells serve a number of roles including mitigation of infection and to stimulate regeneration in response to damage. The transcription factor Cdx2, and to a lesser extent Cdx1, plays essential roles in intestinal homeostasis, and acts as a context-dependent tumour suppressor in colorectal cancer. Deletion of Cdx2 from the murine intestinal epithelium leads to macrophage infiltration resulting in a chronic inflammatory response. However the mechanisms by which Cdx2 loss evokes this response are poorly understood. To better understand this relationship, we used a conditional mouse model lacking all intestinal Cdx function to identify potential target genes which may contribute to this inflammatory phenotype. One such candidate encodes the histocompatability complex protein H2-T3, which functions to regulate intestinal iCD8α lymphocyte activity. We found that Cdx2 occupies the H3-T3 promoter in vivo and directly regulates its expression via a Cdx response element. Loss of Cdx function leads to a rapid and pronounced attenuation of H2-T3, followed by a decrease in iCD8α cell number, an increase in macrophage infiltration and activation of pro-inflammatory cascades. These findings suggest a previously unrecognized role for Cdx in intestinal homeostasis through H2-T3-dependent regulation of iCD8α cells.